Extraordinary temperature dependence of isochoric thermal conductivity of crystalline CO2 doped with inert gases: Cryocrystals - Konstantinov, V.A.; Manzhelii, V.G.; Revyakin, V.P.; Sagan, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The isochoric thermal conductivities of solid (CO2)0.905Kr0.095 and (CO2)1–xXex(x = 0.052 and 0.097) solution of different densities was investigated in the temperature interval from 150 K to the onset of melting. An unusual effect of point defects on the thermal conductivity has been detected. In pure CO2 at T >150 K the isochoric thermal conductivity decreases smoothly with increasing temperature. In contrast, the thermal conductivity of solid CO2/Kr and CO2/Xe solutions first decreases passing through a minimum at 200–210 K and then starts to increase with temperature up to the onset of melting. This behavior of the isochoric thermal conductivity is attributed to the rotation of the CO2 molecules which gains more freedom as the spherically symmetrical inert gas atoms dissolve in CO2.